Analisis Pengaruh Harga Dan Kualitas Produk Smartphone Samsung Terhadap Minat Beli Konsumen Di Delta Cell Matahari Singosaren Surakarta - Saputro, Anton; , Drs. Ma'ruf, M.M (2015)
Purpose in this study was to determine the price has an effect on buying interest on consumers Samsung Smartphone Cell Delta Matahari Singosaren Surakarta, knowing quality product has an effect on the consumer interest in Samsung Smartphone Cell Delta Matahari Singosaren Surakarta. The population in this study is on consumers in the Delta Cell Matahari Singosaren Surakarta, and samples used in this study was taken a sample of 100 respondents. Analysis of data using multiple linear regression test, t test, F test and the coefficient of determination (R2). Based on the results of t test analysis unknown variable price has a significant influence on the buying interest Smartphone Samsung. Quality variable products have a significant impact on buying interest Smartphone Samsung. Based on these results that the most dominant factor in influencing consumer buying interest is the quality of the product.